Intramolecular azavinyl carbene-triggered rearrangement of furans - Makarov, Anton S.; Uchuskin, Maxim G.; Hashmi, A. Stephen K. (Chemical science, 2019)
An intramolecular rhodium-catalyzed reaction of 1-tosyl-1,2,3-triazoles with furans has been explored. The tosylimino functionality was found to play a significant chemical role participating in the subsequent domino-transformations of a key reaction intermediate. One of the reaction pathways leads to valuable 2-formyl- and 2-acetylpyridine building blocks, which could be obtained in one-pot starting from easily accessible (furan-2-ylmethyl)propargyl amines. An original method for the synthesis of highly functionalized indolizines from the obtained pyridines has been proposed.